Leclerc : the growth challenge - Calkins, Tim; Dangles, Julien ([London] : SAGE, 2016)
The senior management team at Leclerc, one of the largest retailers in France, is considering how best to maintain growth in the highly regulated French retail industry. Strict limits on pricing and store construction will significantly limit Leclerc's flexibility; many of the traditional growth levers cannot be used. These regulations also have a major impact on competition. The executives at Leclerc must identify the optimal growth plan and then consider whether it will deliver the desired growth.
Originally Published in: Calkins, T., & Dangles, J. (2009). Leclerc: The Growth Challenge. 5-109-001. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Leclerc (Market chain); Corporations -- Growth -- Case studies